Developmental strategy for a new Group A meningococcal conjugate vaccine (MenAfriVacR) - Prasad S. Kulkarni; Suresh S. Jadhav; F. Marc LaForce (Taylor & Francis Group, 2018)
Until recently, periodic Group A meningococcal meningitis outbreaks were a major public health problem in the sub-Saharan Africa. In 2001, the Meningitis Vaccine Project (MVP), a partnership between the World Health Organization (WHO) and PATH, a Seattle-based NGO, and the Serum Institute of India Pvt Ltd (SIIPL) initiated discussions aimed at establishing a collaboration to develop a Group A meningococcal conjugate vaccine for this unmet medical need. Over the next 8 years the partnership made countless strategic decisions about product characteristics, raw materials, potential target populations, geographic prioritization and affordability of the vaccine to name a few. These decisions evolved into detailed plans for preclinical development, extensive field trials in Africa and India and a focused regulatory strategy specific for the Men A conjugate vaccine. Important characteristics of the process included, flexibility, transparency andeffective partnerships that included public agencies as well as private companies in Africa, Europe, the United States and India.